La aplicación del Régimen de Detracciones en el Servicio de Transporte de Pasajeros y la necesaria evaluación de su inequidad - Dávila Zúñiga, Giovanna Maritza (2021)
The topic raised in this thesis is the impact of the principle of consistency and taxpaying capacity by including the passenger land transportation service within the “detracciones” system. This is due to the fact that although the original purpose of the “detracciones” (withholding tax) regime is to collect the General Sales Tax in advance through the customer’s payment of the amount withheld as a deposit into a special supplier’s bank account, operations have been included without a differentiated treatment with the course of time. This is the case of the passenger land transportation service despite not being subject to taxes (because of being exempt). Likewise, the assessment of the “detracciones” amount is made based on the axles of the vehicles that pass through the toll gates at the national level, whereas for the rest of the operations, the Tax Liabilities of the Payment System (SPOT) are calculated by applying a percentage on the value of the operation. We clearly see that the principle of consistency and taxpaying capacity is not being applied, for which, this sector is being affected. Although the legislator would have sought its formalization by including it in the system, it does not take into account the effective taxation of this sector regarding taxes other than the General Sales Tax to which the existing funds in the “detracciones” bank account can be applied, as well as the various existing restrictions for the release of such funds. Thus, by applying the SPOT to a service that is not taxed with the IGV, it harms the liquidity of these companies. In conclusion, I consider that the rule that includes the service mentioned lines above in the “detracciones” system must be revised and/or annulled for not complying with the principle of consistency and taxpaying capacity. This is because such service is exempt from the General Sales Tax payment and the additional “detracciones” payment is different from all those subject to the SPOT.